2000
DOI: 10.1097/00005392-200007000-00060
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neurokinin Receptors in the Behavioral Effect of Intravesical Antigen Infusion in Guinea Pig Bladder

Abstract: These results suggest a role for activation of NK1 and NK2, but not NK3 receptors, by tachykinins released from capsaicin-sensitive nerves, in the increased abdominal licking behavior response of guinea pigs to intravesical antigen infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Recently it has been shown that TKs enhance the activity of N-and L-type calcium channels through the stimulation of NK 2 receptors in isolated small to medium size dorsal root ganglia neurons, providing further evidence for the neuronal expression of these receptors (Sculptorenau and De Groat, 2003). There is behavioral (Ruggieri et al, 2000), cystometrical (Lecci and Maggi, 2001), and immunohistochemical (Kiss et al, 2001) evidence that NK 2 receptors expressed on bladder afferent neurons are stimulated during bladder irritation, but they do not play an important role in signaling the bladder status under physiological conditions. Given these premises, it is not surprising that the blockade of NK 2 receptors reduces the amplitude and frequency of non-voiding contractions occurring during the filling phase of cystometry in chronically spinal cord-transected rats (Abdel-Gawad et al, 2001;Abdel-Karim et al, 2002).…”
Section: Urinary Bladdermentioning
confidence: 96%
“…Recently it has been shown that TKs enhance the activity of N-and L-type calcium channels through the stimulation of NK 2 receptors in isolated small to medium size dorsal root ganglia neurons, providing further evidence for the neuronal expression of these receptors (Sculptorenau and De Groat, 2003). There is behavioral (Ruggieri et al, 2000), cystometrical (Lecci and Maggi, 2001), and immunohistochemical (Kiss et al, 2001) evidence that NK 2 receptors expressed on bladder afferent neurons are stimulated during bladder irritation, but they do not play an important role in signaling the bladder status under physiological conditions. Given these premises, it is not surprising that the blockade of NK 2 receptors reduces the amplitude and frequency of non-voiding contractions occurring during the filling phase of cystometry in chronically spinal cord-transected rats (Abdel-Gawad et al, 2001;Abdel-Karim et al, 2002).…”
Section: Urinary Bladdermentioning
confidence: 96%
“…The access catheters used in complex surgical operations have different structures depending on the target organ. These types of catheters can be referred to as surgical catheters, which contain diagnostic catheters and therapeutic catheters. Surgical catheters can be used to diagnose and treat diseases of the urinary system, cardiovascular diseases of the circulatory system, diseases of the gastrointestinal and digestive system, and diseases of the nervous system. For example, surgical catheters used for minimally invasive urological diagnosis and treatment include ultrasound detection catheters for prostate cancer (Figure h), ablation catheters for bladder tumors, balloon catheters for stones, and microcatheters for the treatment of cystitis by drug injection, among others.…”
Section: Clinical Catheter-based Surgical Instrumentsmentioning
confidence: 99%